The TGARCH Supply Chain Management Model of Rice Price Volatility in South Sumatra, Indonesia - Lastinawati, Endang; Mulyana, Andy; Zahri, Imron; Sriati, Sriati (International Journal of Supply Chain Management, 2020)
The aim of this study was to build a price model for premium and medium rice in South Sumatra Province, being a major centre for production in Indonesia. This was estimated using the ARCH/GARCH model, based on the weekly data obtained between March 2016 and July 2019. The results showed the occurrence of price volatility for premium and medium variety, despite the polity implementation by government. Therefore, the best volatility model was identified, termed TGARCH (1,1), with a threshold of 1, characterized by futuristic price predictability. In addition, the estimations provide an overview, and also serve as a material for policy evaluation, in order to enhance effectivity and promote the actualization of goals.